2021
DOI: 10.1126/sciadv.abj3066
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-1D exciton channels in strain-engineered 2D materials

Abstract: Nanowires induce mechanical deformations in monolayer semiconductors, creating potential channels that guide optical excitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 64 publications
0
56
0
Order By: Relevance
“…The strain was applied along both lattice vectors and , where a is the lattice constant, which is equivalent to modifying the lattice constant by a = (1 + ε ) a 0 , where a 0 the lattice constant for the unstrained structure and ε the strain magnitude. 49 The A exciton ( E A = 1.58 eV) and dark exciton ( E D = 1.55 eV) energies 13 for the unstrained structure are expected to red-shift upon strain application, as discussed for the nano-indented wrinkle. The energy dependence on strain for the A exciton and lowest dark exciton (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The strain was applied along both lattice vectors and , where a is the lattice constant, which is equivalent to modifying the lattice constant by a = (1 + ε ) a 0 , where a 0 the lattice constant for the unstrained structure and ε the strain magnitude. 49 The A exciton ( E A = 1.58 eV) and dark exciton ( E D = 1.55 eV) energies 13 for the unstrained structure are expected to red-shift upon strain application, as discussed for the nano-indented wrinkle. The energy dependence on strain for the A exciton and lowest dark exciton (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…1,2 Strain engineering is a powerful tool to control the physical properties of few layers of TMDCs and consequently it could be used for the development of strain based devices. [3][4][5][6][7][8][9] TMDCs can support large strain fields before they rupture which could open new opportunities for novel 2D devices. 4 It was previously shown that the presence of strain can change considerably the optical properties of ML TMDCs due to the change in band-gap, even inducing a direct to indirect transition.…”
Section: Introductionmentioning
confidence: 99%
“…6 Under an external electric field or strain, the electrostatic potential difference and the dielectric screening of materials can be significantly modulated, thereby resulting in condensation of the exciton 7,8 and exciton drift. 9,10 Compared with isotropic materials, excitons exhibit unique optoelectronic properties in anisotropic materials. In monolayer 1T-ReS 2 , the optical oscillator strength along the x-axis is about 800 times that along the y-axis at the absorption edge, and the low-energy bright exciton shows a figure-eight shape polarization.…”
Section: Introductionmentioning
confidence: 99%